The Effect of Liquid Nitrogen on Bone Graft Survival - Sirinoglu, Hakan; Çilingir, Özlem Tuğçe; Çelebiler, Ozhan; Ercan, Feriha; Numanoglu, Ayhan (Facial Plastic Surgery, 2015)
Liquid nitrogen is used in medicine for cancer treatment and tissue preservation; however, bone viability after its application is controversial. This study aims to evaluate both the tissue viability and the clinical and histopathologic findings following liquid nitrogen application with different thawing techniques in rats. Mandibular bone grafts were taken from 45 Wistar rats and freezed in liquid nitrogen for 20 minutes. In the rapid-thawing technique (Rapid Thawing-1, Rapid Thawing-2), the grafts were held for 20 minutes in room temperature; in the slow-thawing technique (Slow Thawing-1, Slow Thawing-2), 20 minutes in −20°C, 20 minutes in +4°C, and 20 minutes in room temperature, respectively. In Rapid Thawing-2 and Slow Thawing-2 groups, autografts were implanted to their origin for 3 weeks and bone staining with India ink was performed and samples taken for histologic examination. The amount of cells and blood vessels and the density of bone canaliculi were significantly reduced in Rapid Thawing-1 and Slow Thawing-1 groups comparing to the Control group. However, the reduction rate was more significant in the Slow Thawing-1 group. Histomorphometric evaluation of the healing autografts after 3 weeks revealed that the decreased amounts of canaliculi were not changed in Slow Thawing-2 group. The study results demonstrated that bone tissue survives after liquid nitrogen treatment regardless of the performed thawing technique; however, slow thawing causes more tissue damage and metabolism impairment.
Keywords: liquid nitrogen; cryosurgery; bone tissue; thawing speed; bone graft viability